2020
DOI: 10.30649/obj.v3i1.31
|View full text |Cite
|
Sign up to set email alerts
|

Seorang Penderita SLE dengan Emboli Paru Akut dan Hipertensi Pulmonal (Studi Kasus)

Abstract: <p>Kondisi <em>Pulmonary embolism</em> (PE) merupakan bagian dari spektrum penyakit yang disebut <em>Venous thromboembolism</em> (VTE).  Seorang pasien dengan keluhan utama batuk yang mengeluarkan dahak berwarna keputihan datang ke RSUP Sanglah, Bali untuk mendapatkan terapi. Riwayat sebelumnya, pasien pernah dirawat inap di RSUP Sanglah tersebut.</p><p>Saat ini diagnosis akhir pasien ini: SLE <em>on treatment</em> dengan <em>moderate pulmonary hipert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Based on the condition ARDS can occur in all age groups, from children to adults. The incidence of ARDS increases with age, ranging from 16 cases per 100,000 per year in the age range 15-19 years and increasing to 306 cases per 100,000 per year in the age range 75-84 years (Andisari et al, 2020).…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the condition ARDS can occur in all age groups, from children to adults. The incidence of ARDS increases with age, ranging from 16 cases per 100,000 per year in the age range 15-19 years and increasing to 306 cases per 100,000 per year in the age range 75-84 years (Andisari et al, 2020).…”
Section: Epidemiologymentioning
confidence: 99%
“…In Indonesia, ARDS is still underdiagnosed. the study of Bellani and colleagues showed that clinicians recognized or diagnosed as many as 60.2% of patients with ARDS.3 ARDS can cause sepsis and multiorgan failure that can lead to death so, in its management, clinicians must be faster and more responsive in dealing with ARDS (Andisari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%